Intravenous Neuromyelitis Optica Autoantibody in Mice Targets Aquaporin-4 in Peripheral Organs and Area Postrema - Ratelade, Julien (Public Library of Science, 2011)
The pathogenesis of neuromyelitis optica (NMO) involves binding of IgG autoantibodies (NMO-IgG) to aquaporin-4 (AQP4) on astrocytes in the central nervous system (CNS). We studied the in vivo processing in mice of a recombinant monoclonal human NMO-IgG that binds strongly to mouse AQP4. Following intravenous administration, serum [NMO-IgG] decreased with t(1/2) ∼18 hours in wildtype mice and ∼41 hours in AQP4 knockout mice. NMO-IgG was localized to AQP4-expressing cell membranes in kidney (collecting duct), skeletal muscle, trachea (epithelial cells) and stomach (parietal cells). NMO-IgG was seen on astrocytes in the area postrema in brain, but not elsewhere in brain, spinal cord, optic nerve or retina. Intravenously administered NMO-IgG was also seen in brain following mechanical disruption of the blood-brain barrier. Selective cellular localization was not found for control (non-NMO) IgG, or for NMO-IgG in AQP4 knockout mice. NMO-IgG injected directly into brain parenchyma diffused over an area of ∼5 mm(2) over 24 hours and targeted astrocyte foot-processes. Our data establish NMO-IgG pharmacokinetics and tissue distribution in mice. The rapid access of serum NMO-IgG to AQP4 in peripheral organs but not the CNS indicates that restricted antibody access cannot account for the absence of NMO pathology in peripheral organs.